PENGARUH KONSENTRASI DAN SUHU LARUTAN OSMOTIK TERHADAP PENYUSUTAN VOLUME, KEKERASAN DAN WARNA PADA BUAH NAGA - Spetriani; Siti Fathurahmi (Jurnal Pengolahan Pangan, 2019)
Osmotic dehydration is one of the methods in making of intermediate moisture food. Osmotic dehydration is done by immersing the material in a osmotic solution in the form of a sugar solution. The purpose of this research is to investigate the effect of concentration and temperature of osmotic solution on volume shrinkage, hardness and color change during the process of osmotic dehydration of dragon fruit.Dragon fruit has been immersed in osmotic solution with varying concentrations of 30 oBrix, 50 oBrix, and 70 oBrix and a solution temperature of 30 oC, 40 oC, and 50 oC. The average value of the largest to the smallest volume shrinkage in succession is in the treatment of 70 oBrix, 50 oBrix, and 30 oBrix. The lowest level of material hardness during osmotic dehydration is found in the treatment of 70 oBrix and 50 oC (B3T3). The CIELAB diagram values ​​show that the average color of the material for all treatments is in the purple-red color column. Based on anova test, the difference in concentration and temperature of the solution did not have a significant effect on the discoloration of dragon fruit after osmotic dehydration.